Proceedings of the 10th World Congress on Engineering Asset Management (WCEAM 2015) - Koskinen, Kari T.; Kortelainen, Helena; Aaltonen, Jussi; Uusitalo, Teuvo; Komonen, Kari; Mathew, Joseph; Laitinen, Jouko (Lecture Notes in Mechanical Engineering, 2016)
This book comprises refereed papers from the 10th World Congress on Engineering Asset Management (WCEAM 2015), held in Tampere, Finland in September 2015. These proceedings include a compilation of state-of-the-art papers covering a comprehensive range of subjects equally relevant to business managers and engineering professionals alike. With a focus on various aspects of engineering asset management ranging from strategic level issues to detail-level machine health issues, these papers address both industry and public sector concerns and issues, as well as advanced academic research. Proceedings of the WCEAM 2015 is an excellent reference and resource for asset management practitioners, researchers and academics, as well as undergraduate and postgraduate students at tertiary institutions or in the industry.